General, organic, and biochemistry - Denniston, Katherine J. (McGraw-Hill Higher Education, 2004)
The fourth edition of General, Organic, and Biochemistry is designed to help undergraduate health-related majors and students of all other majors understand key concepts and appreciate the significant connections between chemistry, health, disease, and the treatment of disease. This text strikes a balance between theoretical and practical chemistry, while emphasizing material that is unique to health-related studies.